Use of Anti-VEGF Agents in Glaucoma Surgery. (27th June 2017) - Slabaugh, Mark; Salim, Sarwat
Abstract : A number of antivascular endothelial growth factor agents are currently available to treat various ocular conditions. These agents have similar, but distinct, biologic qualities and have been explored in the management of neovascular glaucoma and in glaucoma surgery. Several different delivery methods are described, and because these medications are routinely given as intraocular injections, some benefits over traditional antifibrotic medications when used in glaucoma surgery are noted. These agents effectively induce regression of anterior segment neovascularization and facilitate initial surgical management of neovascular glaucoma, but the long-term outcome of this condition remains dependent on definitive management of the underlying process. Use in trabeculectomy or tube shunt procedures for other types of glaucoma has shown promise in modulating bleb morphology but has not yet been found to be as effective as traditional antifibrotic agents. There are reports of persistently raised intraocular pressure after repeated use of the anti-VEGF agents, possibly related to frequency of injection. These medications have wide application in the field of surgical glaucoma, but a definitive role has yet to be defined.